Ten Years of Tax Audit Research on Sinta-Indexed Journals: A Literature Review Approach - Hartanto, Anton Dwi; Tjaraka, Heru (Universitas Negeri Padang, 2025)
This study aims to provide a framework of thinking about the role of tax audits and to find future research opportunities. This study analyzed 84 articles related to tax audits from 53 Sinta-indexed journals in the last ten years (2014-2023). Quantitative research with Correlational Research is the most widely used research method. Research findings show that competence, independence, information systems, task complexity, and tax audit deadlines affect tax audits. Meanwhile, tax audits affect tax avoidance, tax evasion, VAT restitution, tax compliance, tax revenue, and firm value. For future research, the topic of tax audit can be conducted in phenomenological qualitative research or mixed-method research. For quantitative approach, tax audit can be served as a mediating or intervening variable.